Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes

Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

Summer season and long-term drought increase the richness of bacteria and fungi in the foliar phyllosphere of Quercus ilex in a mixed Mediterranean forest - Penuelas, J; Rico, L; Ogaya, R; Jump, A S; Terradas, J (Plant Biology, 2012)
We explored the changes in richness, diversity and evenness of epiphytic (on the leaf surface) and endophytic (within leaf tissues) bacteria and fungi in the foliar phyllosphere of Quercus ilex, the dominant tree species of Mediterranean forests. Bacteria and fungi were assessed during ontogenic development of the leaves, from the wet spring to the dry summer season in control plots and in plots subjected to drought conditions mimicking those projected for future decades. Our aim was to monitor succession in microbiota during the colonisation of plant leaves and its response to climate change. Ontogeny and seasonality exerted a strong influence on richness and diversity of the microbial phyllosphere community, which decreased in summer in the whole leaf and increased in summer in the epiphytic phyllosphere. Drought precluded the decrease in whole leaf phyllosphere diversity and increased the rise in the epiphytic phyllosphere. Both whole leaf bacterial and fungal richness decreased with the decrease in physiological activity and productivity of the summer season in control trees. As expected, the richness of epiphytic bacteria and fungi increased in summer after increasing time of colonisation. Under summer dry conditions, there was a positive relationship between TRF (terminal restriction fragments) richness and drought, both for whole leaf and epiphytic phyllosphere, and especially for fungal communities. These results demonstrate that changes in climate are likely to significantly alter microbial abundance and composition of the phyllosphere. Given the diverse functions and large number of phyllospheric microbes, the potential functional implications of such community shifts warrant exploration.
Keywords: Bacteria; Bacteria: genetics; Bacteria: growth & development; Bacterial; Bacterial TRF richness; Bacterial: genetics; Biodiversity; colonisation time; DNA; Drought; Droughts; endophytes; epiphytes; foliar and epiphytic microbial diversity; foliar phyllosphere; Fungal; fungal TRF richness; Fungal: genetics; fungi; Fungi: genetics; Fungi: growth & development; Mediterranean Region; Plant Leaves; Plant Leaves: microbiology; Polymorphism; Quercus; Quercus: microbiology; Restriction Fragment Length; Seasonality; Seasons; Trees; Trees: microbiology

Do photosynthetic limitations of evergreen Quercus ilex leaves change with long-term increased drought severity? - Limousin, Jean-Marc; Misson, Laurent; LAVOIR, ANNE-VIOLETTE; MARTIN, NICOLAS K.; Rambal, Serge (Plant, Cell & Environment, 2010)
Seasonal drought can severely impact leaf photosynthetic capacity. This is particularly important for Mediterranean forests, where precipitation is expected to decrease as a consequence of climate change. Impacts of increased drought on the photosynthetic capacity of the evergreen Quercus ilex were studied for two years in a mature forest submitted to long-term throughfall exclusion. Gas exchange and chlorophyll fluorescence were measured on two successive leaf cohorts in a control and a dry plot. Exclusion significantly reduced leaf water potential in the dry treatment. In both treatments, light-saturated net assimilation rate (Amax), stomatal conductance (gs), maximum carboxylation rate (Vcmax), maximum rate of electron transport (Jmax), mesophyll conductance to CO2 (gm) and nitrogen investment in photosynthesis decreased markedly with soil water limitation during summer. The relationships between leaf photosynthetic parameters and leaf water potential remained identical in the two treatments. Leaf and canopy acclimation to progressive, long-term drought occurred through changes in leaf area index, leaf mass per area and leaf chemical composition, but not through modifications of physiological parameters.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acclimation; Drought; Mediterranean evergreen; mesophyll conductance; photo- synthetic capacity; photosynthesis limitation; Seasonality; throughfall exclusion

Seasonality of monoterpene emission potentials in Quercus ilex and Pinus pinea: Implications for regional VOC emissions modeling - KEENAN, Trevor; Niinemets, Ülo; Sabaté, Santi; Gracia, Carlos; Penuelas, Josep (Journal of Geophysical Research: Atmospheres, 2009)
VOC emissions from terrestrial ecosystems provide one of the principal controls over oxidative photochemistry in the lower atmosphere and the resulting air pollution. Such atmospheric processes have strong seasonal cycles. Although similar seasonal cycles in VOC emissions from terrestrial ecosystems have been reported, regional emissions inventories generally omit the effect of seasonality on emissions. We compiled measurement data on seasonal variations in monoterpene emissions potentials for two evergreen species (Quercus ilex and Pinus pinea) and used these data to construct two contrasting seasonal response functions for the inclusion in monoterpene emission models. We included these responses in the Niinemets et al. model and compared simulation results to those of the MEGAN model, both with and without its predicted seasonality. The effect of seasonality on regional monoterpene emissions inventories for European Mediterranean forests dominated by these species was tested for both models, using the GOTILWA+ biosphere model platform. The consideration of seasonality in the Niinemets et al. model reduced total estimated annual monoterpene emissions by up to 65% in some regions, with largest reductions at lower latitudes. The MEGAN model demonstrated a much weaker seasonal response than that in the Niinemets et al. model, and did not capture the between species seasonality differences found in this study. Results suggest that previous regional model inventories based on one fixed emission factor likely overestimate regional emissions, and species-specific expressions of seasonality may be necessary. The consideration of seasonality both largely reduces monoterpene emissions estimates, and changes their expected seasonal distribution.
Keywords: Holm oak; Italian stone pine; Models; regional inventory; Seasonality; VOC emissions

Process-based modelling of isoprenoid emissions from evergreen leaves of Quercus ilex (L.) - Grote, R; Mayrhofer, S; Fischbach, R J; Steinbrecher, R; Staudt, M; Schnitzler, J.-P. (Atmospheric Environment, 2006)
Monoterpenes play an important role in regulating the trace gas composition of the lower troposphere. Therefore, realistic estimates of the daily as well as seasonal variations of monoterpene emission source strength on the Earth surface are required. Monoterpenes are emitted by Holm oak (Quercus ilex L.) and other species lacking speciﬁc foliar terpene storage structures and their development is dependent on light and temperature. In the present work we describe a process-based emission model taking into account the physiological/phenological state of Holm oak leaves and biochemical processes leading to the formation of monoterpenes. The model ‘seasonal isoprenoid synthase model–biochemical isoprenoid biosynthesis model’ (SIM–BIM2) is developed based on a previous version which was used to simulate isoprene emissions from deciduous oaks. The current model considers additional enzymatic reactions in Holm oak chloroplasts that lead to the formation of monoterpenes. The comparison of simulated and measured biochemical properties as well as emission rates displayed that the ability of the model to dynamically adjust monoterpene biosynthesis capacity by modulating the amount of monoterpene synthase activities in dependence of the weather pattern led to realistic simulations of light-dependent monoterpene emission rates. Differences to simulation results obtained by a widely used alternative model [Guenther, A.B., Zimmerman, P.R., Harley, P.C., Monson, R.K., Fall, R., 1993. Isoprene and monoterpene emission rate variability—model evaluations and sensitivity analyses. Journal of Geophysical Research 98, 12609–12617] are discussed.
Keywords: model development; monoterpene emission rates; monoterpene synthases; Quercus ilex; Seasonality; sim-bim2

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A.; François, L.; Ghislain, M.; Cheddadi, R. (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A; François, L; Ghislain, M; Cheddadi, R (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Seasonal patterns of terpene content and emission from seven Mediterranean woody species in field conditions - Llusia, J.; Penuelas, J. (AMERICAN JOURNAL OF BOTANY, 2000)
The seasonal pattern of terpene content and emission by seven Mediterranean woody species was studied under field conditions. Emission rates were normalized at 30 degrees C and 1000 mu mol.m(-2).s(-1) PFD (photosynthetic photon Aux density). Bupleurum fruticosum, Pinus halepensis, and Cistus albidus stored large amounts of terpenes (0.01-1.77% \{[\}dry matter]) with maximum values in autumn and minimum values in spring. They emitted large amounts of terpenes (2-40 mu g.g DM-1.h(-1)), but with no clear seasonal trend except for Cistus albidus, which had maximum values in spring and minimum values in autumn. The nonstoring species Arbutus unedo, Erica arborea, Quercus coccifera and Quercus ilex also emitted large amounts of terpenes (0-40 mu g.g DM-1.h(-1)) and also tended to present maximum emission rates in spring, although this trend was significant only for A. unedo. At the seasonal scale, emission rates did not follow changes in photosynthetic rates; instead, they mostly followed changes in temperature. From autumn to spring, the least volatile monoterpenes such as limonene were emitted at highest rates, whereas the most volatile monoterpenes such as ol-pinene and P-pinene were the most emitted in summer. The monoterpene emission rates represented a greater percentage of the photosynthetic carbon fixation in summer (from 0.51% in Arbutus unedo to 5.64% in Quercus coccifera) than in the rest of the seasons. All these seasonality trends must be considered when inventorying and modeling annual emission rates in Mediterranean ecosystems.
The following values have no corresponding Zotero field: pub-location: OHIO STATE UNIV-DEPT BOTANY 1735 NEIL AVE, COLUMBUS, OH 43210 USA publisher: BOTANICAL SOC AMER INC
Keywords: alpha-pinene; limonene; mediterranean woody species; photosynthetic rate; relative humidity; Seasonality; Temperature; terpene emission and storage; volatility

Factors affecting movements and home ranges in the jay (Garrulus glandarius) - Rolando, Antonio (Journal of Zoology, 1998)
The winter home ranges, movements and density of the jay Garrulus glandarius in the Maremma Natural Park (Tuscany, Italy) are presented, and compared with those already known for the other seasons. The movements of jays were studied for short periods over 6 years by radiotelemetric techniques (26 home ranges), direct observations of movements from vantage points, and transect counts. Summer and autumn ranges were much larger than spring and winter ones. Incremental area plots and auto-overlap analyses showed that, on average, spring ranges increased in area with time without shifting, whereas winter ranges were rather stable. In both periods, however, some birds moved as floaters since the degree of range auto-overlap decreased significantly with time. In winter and spring, range sizes of jays inhabiting different habitats were significantly different, being larger in sites with higher habitat heterogeneity. The structure of home ranges was variable in all seasons; birds showed jointed and disjointed ranges, with one or more activity centres, in all the possible combinations. In every season the average degree of range overlap between jays caught at the same site was rather high and overall actual overlap, when non-tagged birds were also considered, was even higher. No territorial behaviour was ever observed. During summer jays moved into the pinewood for the greater part of the day to collect cicadas, Cicada orni, and returned to the maquis in the evening. During autumn birds regularly moved within the maquis or from the maquis to the pinewood to cache oak (Quercus ilex) acorns. No regular long movements between habitats were observed during spring and winter. Direct observations and analyses of pellets suggested that food was abundant and highly diversified throughout the year. Thus, seasonal movements and home ranges were flexible and mainly controlled by food availability and its distribution in space and time.
Keywords: home range; jay; movements; radiotelemetry; Seasonality

Environmental control of CO2 assimilation rates and stomatal conductance in five oak species growing under field conditions in Greece - Radoglou, K (Ann. For. Sci., 1996)
The present study compared CO2 assimilation rate and stomatal conductance of five oak species from the beginning of May through November 1993 under similar natural conditions. Gas exchange, leaf characteristics and water status were measured on 30-year-old Quercus ilex, Q macrolepis, Q pedunculiflora, Q pubescens and Q trojana growing in experimental plots in northern Greece. The seasonal pattern of assimilation rates was similar for all study species but differences occurred between the species. After initial leaf expansion, all species rapidly developed high photosynthetic rates. In addition, assimilation rates were high in all species in May and November after rain events. No significant differences in stomatal conductance were observed among species during the growing season. The relationships between assimilation rate and stomatal conductance displayed variation in the slopes among species and months.
Keywords: assimilation rate; Drought; Quercus sp; Seasonality; Stomatal conductance